Analisis Dampak Positif Transformasi Kinerja Divisi AUM PT PLN IP UBP Keramasan - Safitri, Ayu Dwi; Almigo, Nuzsep (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
Performance transformation is a systematic change process aimed at altering work methods, mindsets, organizational structure, and the utilization of technology to achieve higher levels of efficiency and effectiveness. The methods used in this community service activity included observation and the distribution of a Likert-scale questionnaire to gather information from employees in the Administrative and General Division of PT PLN IP UBP Keramasan.The results of the community service conducted at the PT PLN IP UBP office indicate that the performance transformation implemented in the AUM Division of PT PLN Indonesia Power UBP Keramasan has had a significantly positive impact. This is reflected in the high average respondent scores (mean 4.05–4.45), strong item validity (Pearson correlation > 0.444, p < 0.05), and very high instrument reliability (Cronbach’s Alpha = 0.966). These findings demonstrate that the transformation has been well-received by employees and has contributed to improved efficiency and a more productive work culture.